DISEASE PROBlEMS IN SHRIMP SECTOR IN KHUlNA DISTRICT OF BANGlADESH: A QUESTION OF SUSTAINABIUTY - Faruque, A.M. 0.; Ahmed, G. U.; Hasan, M. R.; Hossain, M. A. (Journal of Indian Fisheries Association, 2008)
Disease is the main restraining factor for the development of shrimp sector in Bangladesh. Both brackish water shrimp bagda (Penaeus monodon} and freshwater prawn golda, (Macrobrachiumrosenberg#) farming in Bangladesh have been facing disease problem. A study on disease outbreak in both brackish water and freshwater small-scale shrimp farms (gher) in Khulna district was carried out through interviewing randomly selected 3-5% of shrimp farmers with a structuredquestionnaire during March to December, 2002. The study showed that 97% bagda farming ghers and 80% golda farming ghers were affected by disease. White spot disease was the severe disease for bagda, whereas, antenna rot was the main disease for freshwater prawn. Change of water and liming were carried out as control measures of disease for bagda shrimp farming, while it was only liming for golda farming. A small number of shrimp farmers (15%) used chemicals for treatment of shrimp diseases. Development of suitable farming technology to prevent disease contamination and innovation of proper treatments for diseases are required to overcome the disease problems for sustainable shrimp farming in Bangladesh.Keywords: Disease, bagda, golda, gher.